The male complaint: the manosphere and misogyny online - Copland, Simon (Polity, 2025)
"Inspired by leaders such as Andrew Tate and Jordan Peterson, the online Manosphere has exploded in recent years. Dedicated to anti-feminism, these communities have orchestrated online campaigns of misogynistic harassment, with some individuals going as far as committing violent terrorist attacks. Although the Manosphere has become a focus point of the media, researchers and governments alike, discussions tend to either over-sensationalize the community or offer simplistic explanations for their existence. This book uses a mixture of historical and economic analysis, alongside actual Manosphere content, to delve deeper. With The Male Complaint, Simon James Copland explains how the Manosphere has developed and why it appeals to so many men. He argues that the Manosphere is not an aberration, but is deeply embedded within mainstream, neoliberal, social structures. For a cohort of alienated men, the promise of community provides a space of understanding, connection and purpose. This insightful book dares to dig into the corners of incel communities and online spaces where misogyny thrives. It is essential reading for anyone who wants to understand, and do something about, this growing and worrying phenomenon." -- Amazon.com